Cannabis intoxication after accidental ingestion in infants: urine and plasma concentrations of Δ-9-tetrahydrocannabinol (THC), THC-COOH and 11-OH-THC in 10 patients. (3rd May 2020) - Guidet, Charles; Gregoire, Matthieu; Le Dreau, Alexiane; Vrignaud, Benedicte; Deslandes, Guillaume; Monteil-Ganière, Catherine
Abstract: Introduction: Accidental cannabis poisoning after oral ingestion in infants is an emerging cause of intoxication with well-known clinical aspects but few data exist regarding the levels of cannabinoids in plasma and urine. Here, we present data on the concentrations of Δ-9-tetrahydrocannabinol (THC) and metabolites in plasma and/or urine in 10 infants after cannabis intoxication. Materials and methods: Cannabinoids were detected using an automated immunochemical method and quantified using liquid chromatography coupled with mass spectrometry. Results: Ten infants were admitted after cannabis poisoning. THC, THC-COOH and 11-OH-THC plasma levels ranged from 4.4 to 127 ng/mL, from 28 to 433 ng/mL and from 2 to 59.8 ng/mL, respectively. THC-COOH urine levels ranged from 748 to 5689 ng/mL. The most common symptoms were drowsiness, hypotonia, behavioural disorder and tachycardia. Discussion: No correlation between plasma concentrations and symptoms could be found, but the concentration of THC-COOH in the two patients who experienced seizures was higher than 3000 ng/mL. This series of cases of accidental intoxication in infants showed high THC and metabolites concentrations in urine and plasma.